2005
DOI: 10.1080/10903120590891688
|View full text |Cite
|
Sign up to set email alerts
|

Errors of Omission in the Treatment of Prehospital Chest Pain Patients

Abstract: Paramedics may delay transport of patients with potential cardiac ischemia. Deviations from protocol occur frequently and the care documented for prehospital patients with chest pain is variable. The expected care described by written protocols does not correlate with the treatment documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…These rates are consistent with previous studies conducted in other settings that have shown similarly poor adherence rates to OOH chest pain protocols, even for patients with suspected cardiac ischemia. [30][31][32] These findings suggest that OOH providers may exercise significant discretionary decision-making for patients with chest pain, which in turn may help explain why the presence of both local and statewide protocols do not attenuate disparities in care.…”
Section: Discussionmentioning
confidence: 94%
“…These rates are consistent with previous studies conducted in other settings that have shown similarly poor adherence rates to OOH chest pain protocols, even for patients with suspected cardiac ischemia. [30][31][32] These findings suggest that OOH providers may exercise significant discretionary decision-making for patients with chest pain, which in turn may help explain why the presence of both local and statewide protocols do not attenuate disparities in care.…”
Section: Discussionmentioning
confidence: 94%
“…The difference was not statistically significant (p = 0.730), but it gives a hint about the DSTs impact on the time spent in hospital before definitive care. 60,61 In addition, one study aimed to evaluate if paramedics could be helpful in determining if patients required emergency care showed paramedics failed to predict which patients do and do not require ED care. 62 One of the main findings is the lack of RCTs in evaluation of DSTs in prehospital care.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has indicated that deviations from protocols were common and that the care documented for pre-hospital patients with chest pain was variable [58].…”
Section: Influence Of Demographic Variables On Pre-hospital Treatmentmentioning
confidence: 99%